HEV Infection as an Aetiologic Factor for Acute Hepatitis: Experience from a Tertiary Hospital in Bangladesh (Journal of Health, Population and Nutrition, 2009)
Acute hepatitis is seen sporadically round the year in Bangladesh. The incidence of acute viral hepatitis E increases after floods as this allows sewerage contamination of piped and groundwater. The aim of this retrospective study was to assess the burden of hepatitis E virus (HEV infection) in Bangladesh. Patients attending the Hepatology Unit III of the Bangabandhu Sheikh Mujib Medical University, during June 2004-December 2006, were included in the study. All viral markers were tested by enzyme-linked immunosorbent assay. The study population was divided in four groups. Group 1 included 144 patients with acute viral hepatitis. The inclusion criteria were: nausea and/or vomiting, loss of appetite, serum bilirubin >200 μmol/L, raised serum transaminases, and prothrombin time >3 seconds prolonged beyond control value. In Group 2, there were 31 pregnant women with acute viral hepatitis. All the patients had prodrome, icterus, raised serum bilirubin and raised serum transaminase levels. Group 3 included 23 patients presenting with fulminant hepatic failure. In Group 4, 69 patients with cirrhosis of liver were included. They presented with features of decompensation for the first time. The inclusion criteria were: patients with established cirrhosis with jaundice and/or ascites and/or hepatic encephalopathy. In Group 1, 58.33% of the 144 patients had acute viral hepatitis E. In Group 2, 45.16% of the pregnant women also had acute viral hepatitis E. HEV was responsible for 56.52% cases of fulminant hepatic failure in Group 3. In 21.7% cases in Group 4, decompensation of cirrhosis was due to HEV. Acute viral hepatitis E in the third trimester of pregnancy and HEV-induced fulminant hepatic failure were associated with 80% of mortality despite the best possible care. In this clinical context, acute viral hepatitis E is the leading cause of wide spectrum of liver disease ranging from severe acute viral hepatitis, fulminant hepatic failure, to decompensation of liver in cirrhotics in Bangladesh. Sewerage contamination of piped water following floods may contribute to the higher incidence of HEV infection. Key words: Hepatitis; Hepatitis E infections; Hepatitis E virus; Retrospective studies; Bangladesh doi: 10.3329/jhpn.v27i1.3314 J Health Popul Nutr 2009 Feb;27(1):14-19